Examining the Relationship Between Brand Satisfaction and Customer Experience in Nepal's Retail Banking Sector - Karna, Poonam Kumari Labh (Mikailalsys Journal of Mathematics and Statistics, 2025)
This study examines the primary determinants of customer happiness and loyalty in Nepal's competitive retail banking industry. By integrating insights from primary data and existing literature, this study investigates the effects of situational factors (frequency of bank visits, length of customer-bank relationship) and service quality dimensions (tangibility, reliability, responsiveness, assurance, and empathy) on customer satisfaction and subsequent loyalty. Information was gathered from 575 customers of "A"-class commercial banks in Kathmandu, Nepal, using structured questionnaires. Statistical analysis, such as factor analysis, multiple regression, correlation analysis, and mediation testing (Sobel test), was employed to look into the relationships between the variables. The findings show that elements of service quality, particularly reliability and assurance, have a significant positive impact on customer satisfaction and loyalty. It's interesting to note that while relationship duration positively enhances enjoyment, visit frequency exhibits a negative correlation with it. For banks seeking to enhance customer satisfaction, experience, and enduring loyalty, these insights provide valuable guidance.